2020
DOI: 10.1007/s12471-020-01451-9
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia with no obstructive coronary arteries

Abstract: Ischaemia with no obstructive coronary arteries (INOCA) is a common ischaemic heart disease with a female preponderance, mostly due to underlying coronary vascular dysfunction comprising coronary microvascular dysfunction and/or epicardial coronary vasospasm. Since standard ischaemia detection tests and coronary angiograms are not suitable to diagnose coronary vascular dysfunction, INOCA is often overlooked in current cardiology practice. Future research, including large outcome trials, is much awaited. Yet, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
0
23
0
1
Order By: Relevance
“…An increased incidence is additionally seen in women, with up to 70% of women showing ACS symptoms without CAD demonstrating findings suggestive of CAVS[ 17 - 19 ]. The incidence is particularly high for younger women under the age of 50 years, as well as non-white women[ 20 , 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…An increased incidence is additionally seen in women, with up to 70% of women showing ACS symptoms without CAD demonstrating findings suggestive of CAVS[ 17 - 19 ]. The incidence is particularly high for younger women under the age of 50 years, as well as non-white women[ 20 , 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Current gold standard diagnosis of CAVS utilizes pharmacological provocative testing with high-dose boluses of acetylcholine, ergonovine, or methylergonovine via intracoronary injection[ 2 , 3 , 5 , 13 , 14 ]. The response is then visualized as a coronary vasospasm with transient > 90% occlusion of coronary arteries[ 19 ], during coronary angiography, or via abnormalities of ventricular wall motion on echocardiogram[ 2 , 3 ]. A standard cardiac workup should initially include standard 12-lead electrocardiogram (ECG) during an attack, ambulatory cardiac monitoring, or exercise stress testing to exclude underlying CAD[ 18 ].…”
Section: Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…However in the diagnostic approach to myocardial ischemia in stable angina pectoris, several registries or studies have shown that invasive angiographic procedure of some patients with abnormal noninvasive testing does not always reveal the presence of significant lesions on coronary angiography and it's sometimes susceptible to complications [2] [3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%